Urgensi Santri TPQ Memiliki Akhlak Kepada Guru - Solekhan; Hadi, Syaiful (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Moral education is one of the main teachings of Islam, one of which is morals towards teachers is very important to continue to be taught to students, and must be taught as early as possible. And one of the strategic media to teach it is at the Al-Qur'an Education Park. Given the changing times and the swift influence of cultures outside of Islam which increasingly erodes cultural values and noble Islamic teachings. This is evidenced by the moral decline of the nation's younger generation who have increasingly embraced foreign culture, starting from the style of dress even to their behavior. Including how to behave with the teacher. Therefore, moral education towards teachers in particular becomes urgent to continue to be taught to our younger generation, one of which is through TPQ. With the descriptive method this paper is presented to convey that the urgency of moral education towards teachers, among others, is so that students understand the position of teachers in Islam must be glorified because it is a religious command, teachers are glorified and appreciated because of their enormous contribution in providing knowledge, experience, skills and exemplary, teachers are second parents and high degrees on the side of Allah SWT. And teachers are people who teach obedience to Allah's law even though students sometimes hurt him even though he is still sincere in teaching knowledge to his students.